Supporting Digital Transformation of MSMEs Through Enterprise Architecture Design Using the TOGAF ADM Framework - Sopi; Ukie Tukinah; Ilma Wulansari Hasdiansa; Sitti Hasbiah (Global Research and Collaboration, 2025)
In today’s highly connected and technology-driven environment, digital transformation has become a critical necessity for Micro, Small, and Medium Enterprises (MSMEs) to enhance their competitiveness and long-term sustainability. One strategic approach to facilitate this transformation is through the design of an enterprise architecture tailored to the specific needs of MSMEs. This study aims to develop a structured and adaptive enterprise architecture model for MSMEs by applying the TOGAF ADM (Architecture Development Method) framework. The methodology consists of several key phases: Preliminary, Architecture Vision, Business Architecture, Information Systems Architecture, and Technology Architecture. Each phase provides a systematic approach to assess business requirements, align digital strategies with business goals, and build supporting technological infrastructure. The output of this research is a CompanySpecific Blueprint designed to reflect the actual conditions and operational needs of the targeted MSMEs. This blueprint serves as a comprehensive guide for MSMEs to plan, implement, and manage digital transformation initiatives effectively and progressively. By adopting the TOGAF ADM framework, this research contributes to the development of a responsive and sustainable enterprise architecture model, empowering MSMEs to navigate technological changes and improve their organizational performance. The proposed model is expected to support MSMEs in making informed decisions regarding digital investments, process optimization, and integration of digital tools that align with their strategic objectives.